2022
DOI: 10.21203/rs.3.rs-1670556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gibberellin and abscisic acid transporters facilitate endodermal suberin formation in Arabidopsis

Abstract: The plant hormone gibberellin (GA) regulates multiple developmental processes. It accumulates in the root elongating endodermis, but how it moves into this cell file and the significance of this accumulation are unclear. Here, we identified a monophyletic clade of NPF transporters required for GA and abscisic acid (ABA) translocation. We demonstrate that NPF2.14 is a subcellular GA/ABA transporter, the first to be identified in plants, facilitating GA and ABA accumulation in the root endodermis to regulate sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…However, since the suberization pattern as well as PHO1:H3 expression in myb68 roots was least affected in PPAE and NPAE cells, additional MYB68-independent mechanisms must exists which positively affects suberization decision in the PPAE. This is supported by a recent study which, via a modeling approach, proposed a role for GA in PPAE suberization (Binenbaum, et al, 2023). Moreover, our analyses expands on this model by proposing that the hormonal sensitivity of the XPAE cells is not solely determined by AHP6, but likely also other unknown cytokinin-responseive factors present in the XPAE (Figure 6A).…”
Section: Discussionsupporting
confidence: 86%
“…However, since the suberization pattern as well as PHO1:H3 expression in myb68 roots was least affected in PPAE and NPAE cells, additional MYB68-independent mechanisms must exists which positively affects suberization decision in the PPAE. This is supported by a recent study which, via a modeling approach, proposed a role for GA in PPAE suberization (Binenbaum, et al, 2023). Moreover, our analyses expands on this model by proposing that the hormonal sensitivity of the XPAE cells is not solely determined by AHP6, but likely also other unknown cytokinin-responseive factors present in the XPAE (Figure 6A).…”
Section: Discussionsupporting
confidence: 86%
“…The degradation of DELLA by GA in darkgrown roots releases these TFs and probably triggers transcriptional activation of numerous pathways independently of light. These may include the regulation of root architecture (Castro-Camba et al, 2022), secondary xylem development, lignification (Wang et al, 2017) and endodermal suberin formation (Binenbaum et al, 2023), but not cell elongation. Several DELLA-interacting TFs are involved in GA regulation of cell elongation (de Lucas et al, 2008;Feng et al, 2008;Gallego-Bartolome et al, 2012;Chaiwanon & Wang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is closely related to the aforementioned involvement of ABA in suberization. In addition, it has been reported that gibberellin and ABA accumulate in the root endodermis via NPF2.14 acting as a subcellular transporter, and the accumulated hormones regulate suberization [ 107 ]. However, the regulatory network through in which auxin and GA control suberization remains largely unknown.…”
Section: Suberin Biosynthesis In Plant Roots and Drought-derived Modi...mentioning
confidence: 99%